THE INFLUENCE OF PROFITABILITY, COMPANY SIZE, AND COMPANY ACTIVITY ON THE DISCLOSURE OF SUSTAINABILITY REPORTS IN FOOD AND BEVERAGE SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2020-2023 - Fadilah, Nurul (DAS CONFERENCE INTERNATIONAL SERIES, 2025)
This research aims to determine the influence of profitability, company size, and company activity on the disclosure of sustainability reports. The population in this study consists of food and beverage sub sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. A sample of 10 companies was selected using purposive sampling techniques. data analysis was selected using purposive sampling techniques. Data analysis was conducted using panel data regression with the help of Eviews 12 software. Based on the results of the partial analysis, it shows that the profitability variable has a positive effect on the disclosure of sustainability reports. The company size variable has a negative effect on the disclosure of sustainability reports. The company activity variable no effect on sustainability reports disclosure. And company activity variable have no effect on sustainability report disclosure. Meanwhile, simultaneously profitability, company size and company activities influence the disclosure of sustainability reports.